2009
DOI: 10.1021/ja900285z
|View full text |Cite
|
Sign up to set email alerts
|

Association of Highly Compact Type II Diabetes Related Islet Amyloid Polypeptide Intermediate Species at Physiological Temperature Revealed by Diffusion NMR Spectroscopy

Abstract: Self-association of human islet amyloid polypeptide (hIAPP) is correlated with the development of type II diabetes by the disruption of cellular homeostasis in islet cells through the formation of membrane-active oligomers. The toxic species of hIAPP responsible for membrane damage has not been identified. In this study, we show by pulsed field gradient NMR spectroscopy that the monomeric form of the toxic, amyloidogenic human variant of IAPP (hIAPP) adopts a temperature dependent compact folded conformation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
165
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(193 citation statements)
references
References 80 publications
25
165
3
Order By: Relevance
“…This suggests that the energy of nucleation is high, and the free energy is a relatively steep function of the aggregate size for subnuclear particles (28,40). We note that a similar absence of small oligomers, despite the presence of monomers and large aggregates (ϳ100 nm), has also been observed for another amyloidogenic protein, IAPP (41).…”
Section: Discussionsupporting
confidence: 79%
“…This suggests that the energy of nucleation is high, and the free energy is a relatively steep function of the aggregate size for subnuclear particles (28,40). We note that a similar absence of small oligomers, despite the presence of monomers and large aggregates (ϳ100 nm), has also been observed for another amyloidogenic protein, IAPP (41).…”
Section: Discussionsupporting
confidence: 79%
“…29,70,71,[81][82][83][84] The Aβ barrel is similar to the cytotoxic channel formed by the β-cytolytic antimicrobial PG-1 peptides. Recent studies showed that octameric and decameric β-sheet channels of PG-1 divided into four to five Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not apply to all amyloid channels. Islet amyloid polypeptide (also known as amylin) can induce other membrane pore types, such as toroidal membrane pores, 82 depending on the outward-facing amino acid sequence interacting with the bilayer. Amylin also forms ion channels, as demonstrated in earlier work.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Finally, after 30 h of incubation, the morphology of hIAPPmembrane systems, which consist of rows of cylinders with long-range order in the XY plain, appears to be very similar to the one observed for Ab 1-40 fibrils. [22] A possible mechanism for membrane damage and fibril growth by hIAPP based on our AFM, QCM-D and fluorescence results combined with NMR spectroscopy [23] is shown in Figure 4. From this model emerges a scenario in which the formation of mature fibrils does not appear to be the cause of membrane damage.…”
mentioning
confidence: 92%